P-159 Reflections on delivering a palliative care intervention in english care homes. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Sowerby, Eleanor; Moore, Danni Collingridge; Block, Lieve Van den; Froggatt, Katherine; Payne, Sheila
Abstract : Background: Little is known about the process of implementing new palliative care interventions within care homes. The European Commission-funded PACE research project is a cluster randomised controlled trial of the 'PACE Steps to Success' intervention. Aims: To reflect on the experience of delivering facilitation for implementation of a palliative care intervention in English care homes. Method: Facilitation was delivered to six care homes on a monthly basis over a year by a clinically experienced trainer to staff. The PACE Steps to Success intervention uses a train-the-trainer approach by identifying key staff as PACE coordinators from within each care home. Implementation focused on: preferences for care, assessment, coordination of care, management of symptoms, and care in the last days of life and after death. Data recorded by the facilitator in a reflective diary was explored on the experiences of the site visits, recruitment to the training, implementation, delivery and uptake of the intervention. Factors that supported and hindered the use of the intervention were identified. Results: Supportive factors: Identified PACE coordinators in the care homes helped promote staff engagement and interest in palliative care. The Nursing and Midwifery Council revalidation system motivated staff attendance at training sessions. Certificates were issued following the completion of all taught sessions. Social media was introduced to create a forum for communication and help promote sustainable support and peer networks. Barriers: Barriers to the implementation were changes in the employment of care home managers, coupled with poor communication impacted on recruitment of staff to training sessions and use of new tools. Conclusion : Delivering new interventions in the care home sector is influenced by limited resources and competing pressures on staff. It's possible to implement a palliative care intervention in care homes, when managers are supportive and staff are enabled to work in partnership with the trainer.